Occurence of hypodermosis in Pakistan, Iran and Turkey: comparative risk factor analysis and future perspectives - Ahmed, Haroon; Afzal, Muhammad Sohail; Ozyalin, Ozge; Khan, Mobushir Riaz; Simsek, Sami (J Infection Developing Countries, 2017)
[Abstract Not Available]
Keywords: Hypodermosis; occurence; comparative; risk factor; future perspective